The Influence Of Loading And Unloading Facilities, Development Of Port Technology, And Hr Quality On Service User Satisfaction Which Is Mediated By Service Performance In Parit Rempak Port - Yuwono, Yuwono; Barata, Fausta Ari; Edhie Budi Setiawan, Eduard Alfian Syamsya Sijabat, Dian Artanti Arubusman, (Program Pascasarjana STIE Amkop Makassar, 2024)
The aim of this study is to determine how much influence the variables Loading and Unloading Facilities, Port Technology Development, HR Quality have on Service Performance (Z) in their impact on Service User Satisfaction using the Structural Equation Method (SEM-PLS). Sampling was carried out by distributing questionnaires with purposive sampling to 250 respondents from port service users. The study results show that there are positive and significant results between Port Technology Development and Human Resource Quality on Service Performance; Loading and Unloading Facilities, Quality of Human Resources, and Service Performance on Service User Satisfaction; Service Performance mediates the relationship between Port Technology Development and Service User Satisfaction; Service Performance mediates the relationship between HR Quality and Service User Satisfaction, as well as 3 hypotheses that are rejected, namely Loading and Unloading Facilities have a negative and insignificant effect on Service Performance, Port Technology Development has a positive but not significant effect on Service User Satisfaction, and Service Performance does not mediating the relationship between Loading and Unloading Facilities and Service User Satisfaction at Parit Rempak Port. Keywords: Loading and Unloading Facilities, Port Technology Development, Human Resource Quality, Service User Satisfaction, Service Performance.